Developing Flipbook Multimedia For Learning Motion Photos Techniques For Vocational High School Grade XII - Akhmad Redi Salim; Nurdin Ibrahim; Suyitno Muslim (International Journal of Education, Information Technology, and Others, 2020)
This research is motivated by the fact that the flipbook multimedia using the flipbook maker can make the learning process more effective and also automatically improve student learning outcomes in learning photography. This research develops flipbook media to improve learning on camera movement material based on size (framing) and angle of view (angle). The problems that will be examined in this research are; (1) Produce multimedia learning flipbooks for the subject of image taking, (2) Produce a suitable flipbook learning multimedia for the subject of photography techniques, (3) Produce an effective multimedia learning flipbook for the subject of drawing techniques. This research is a development research. This study developed learning media in the form of a flipbook to make the learning process more effective and to improve student learning outcomes in learning motion picture taking techniques. The data of this study were collected from students at Vocational High School in Tangerang grade XII as an object of research. In collecting data using questionnaire method and documentation. This research is using approacing ADDIE method. The validation results from material experts and media experts were carried out in 2 stages obtained very feasible criteria with a percentage of 85.56% and media experts of 85.56%. The acquisition of material practitioners' results is 90.00% and media practitioners 86.67%. For the response of students to learning media in the form of a digital book based on problem solving to get the score results for Tangerang Vocational High School at 85.00%.